ANTI-DEMOCRACY POLICY OF THE INDONESIAN â€œNEW ORDERâ€ GOVERNMENT ON ISLAM IN 1966-1987 - Siraj, Fuad Mahbub (Journal of Al-Tamaddun, 2019)
This discussion aims to explain further the various policy of the Government of the Republic of Indonesia towards Islam from 1966 to 1987, which led to the occurrence of mutual suspicion between the government and Muslims. The new order government policy on Islam is interesting to discuss, especially to see how the paradigm or the pattern of Islam and the State in 1966-1987 in the New Order government as part of the history and continuity of Islamic thought. The New Order is a democratic order that have commitment to the 1945 Constitution and Pancasila. The New Order is synonymous with democracy and prosperity. However, in the field of Islam in 1966-1987 the opposite of that has occurred, anti-democracy policy shown by the new order government especially on da’wa, Islamic education, Islamic law and religious courts, organizing hajj and the ulema council. The reality in Indonesia shows that Muslims is the majority and the owners of the spirit of dynamics, nationalism and also an intellectual warehouse and in the life of democracy, the number determined and can even direct. Related to this, there is a tendency that the government with all its tactics and strategies trying to control the political life of Muslims. In this context, the government is fully trying, so that the problem of policy issues related to Islam is within its control. Based on that, Muslim in Indonesia felt that the new order government’s policy to Muslim is the pressure to Muslim.